Reconfigurable phase inverter with switchable frequency. Issue 5 (1st March 2017) - Liao, Zhen Heng; Zhang, XuChun
Abstract : A novel reconfigurable phase inverter architecture allowing frequency‐switchable is proposed. Interdigital striplines, metallic via holes, and the defected ground structure are used to obtain 180° phase inverter. The switchable frequency is controlled by the length of the slot‐line on the defected ground which can be changed by PIN‐diodes and a single control voltage. For verification, the simulated and measured results of switchable frequency at 900 MHz and 1.6 GHz phase inverter implemented on microstrip are shown.